English for specific purposes (Music) - San Martín Gómez, Mauricio (2017)
The following textbook develops relevant concepts related to music in English as foreign language. At the same time, learners will learn how to consult and understand different reference sources, give precise opinions on any musical work, comprehend music software terms with ease, and recognize the meaning of expressions and symbols in any score printed in English. Therefore, this material is also meant to aid EFL teachers and translators in planning and designing courses, or looking up key words that are hard to encounter in most dictionaries. At the same time, all kinds of musicians can use this publication as a starting point for an immersion in technical music terms, which will undoubtedly represent an effective academic support. SUGGESTED LANGUAGE PROFICIENCY MINIMUM LEVEL: Intermediate (B1)